Nomadic knowledge in emerging pedagogical contexts: ethnographic experience in two secondary schools in Málaga, Spain. - Cortés-González, Pablo; Rivas-Flores, José Ignacio (Taylor&Francis, 2024)
This paper presents a research experience in secondary schools that develop educational projects of a participatory and transformative nature. This contribution arises from the new educational needs emanating from augmented society and multiple literacies that transform communication and the circulation of knowledge, challenging conventional educational methods. An ethnography was carried out in two secondary schools, one in a rural environment and the other in a metropolitan area. The results are organised around the notion of community; the management processes and shared leadership; and the transformative pedagogical processes that are being developed. We conclude that the Spanish secondary school context is still based on practices centred on content and masterly methodologies; this leads us to understand that the mentioned schools, as disruptive experiences, promote a change towards a curriculum centred on the participation and interests of the students; horizontal and cooperative management practices; a strong sense of community; among others.
https://openpolicyfinder.jisc.ac.uk/id/publication/5236?from=single_hit
Keywords: Enseñanza secundaria; Planificación educativa; Secondary education; Disruptive practices; Educational community; Democratic management